Creative, Integrative and Effective Methods of Phase B Jurisprudence Learning in Islamic Elementary Schools - Dede Iik Mudrikah; Wido Supraha; Budi Handrianto (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The purpose of this article is to present the results of research activities related to formulating creative, integrative and effective methods for teaching Fiqh Phase B. This research activity uses qualitative methods with observation techniques, focus group discussions (FGD) and then the data is triangulated to determine the conclusions drawn by the researcher. . The results of the research activities were that in the creative methods group, flexible and original were the dominant variables for creative methods. The number of groups that expressed this matter was 10 groups. 2 groups only stated that fluency is a variable related to low levels of creative methods, but the majority of groups stated reasons that actually lead to flexibility and originality. In the integrative method group, group work is the dominant variable associated with the integrative method. The number of groups that expressed this matter was 4 groups. 2 groups only stated that role playing was a variable related to low levels of integrative methods. In the effective method group, student responses are the dominant variable related to effective methods. The number of groups that expressed this matter was 4 groups. 1 group only stated that learning activities were a variable related to low levels of effective methods.